2015
DOI: 10.1111/pin.12358
|View full text |Cite
|
Sign up to set email alerts
|

Is ALK‐gene rearrangement overlooked in primary gastrointestinal T‐cell lymphomas? About two cases

Abstract: A 41-year-old male patient with a history of ankylosing spondylitis and Crohn disease, treated with immunomodulators and disease-modifying drugs, was diagnosed with a primary intestinal T-cell lymphoma that followed a 7.5-year-course. This transmural proliferation lacked cytological characteristics of anaplastic large cell lymphoma (ALCL), and was CD8-positive, and CD30- and anaplastic lymphoma kinase (ALK)-negative by immunohistochemistry (IHC). However, ALK-gene rearrangement (ALK-gr) was detected by fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…ITCLD-GI could be transformed into a higher-grade lymphoma[ 18 , 19 , 22 , 26 , 33 , 34 ]. However, the vast majority of CD8+ ITLPD-GI cases show an indolent and lengthy course that lasts for many years or even decades, with a chronic, persistent recurrent or spontaneous remission pattern[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITCLD-GI could be transformed into a higher-grade lymphoma[ 18 , 19 , 22 , 26 , 33 , 34 ]. However, the vast majority of CD8+ ITLPD-GI cases show an indolent and lengthy course that lasts for many years or even decades, with a chronic, persistent recurrent or spontaneous remission pattern[ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors emphasized the importance of performing immunohistochemistry and test for ALK gene rearrangement in all cases of primary gastrointestinal T cell lymphomas, even those lacking an anaplastic histology in view of advances in targeted therapies which could impact treatment and prognosis. 12 Zhang et al reported a primary gastric ALK-negative EBV-negative ALCL in an 82-year-old man who presented with iron deficiency anemia but without any gastrointestinal signs or symptoms. 34 Huang and Li reported a small bowel ALCL in a young HIV patient who presented with small bowel intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have prolonged survival even with no drug treatment, with official recommendations calling for a careful 'watch and Case Report Indolent T cell lymphoproliferative disorder of the gastrointestinal tract: an uncommon case with lymph node involvement and the classic Hodgkin's lymphoma Jie Wu 1# , Long-Guang Li 2# , Xiang-Yan Zhang 1 , Li-Li Wang 1 , Li Zhang 1 , Yu-Jing Xiao 1 , Xiao-Ming Xing 1 , Dong-Liang Lin 1 wait' approach (5)(6)(7)(8)(9)(10)(11). However, a few reports of ITCLD-GTs showed its possibility of transformation to a highergrade lymphoma (12)(13)(14)(15). In the paper by Perry et al there were several patients who had enlarged region lymph nodes but little has been establish about whether ITCLD-GTs could infiltrate these lymph nodes because of the lack of pathological examinations (9).…”
Section: Introductionmentioning
confidence: 99%